Re-estimation of the vertical sensible heat flux by determining the environmental temperature on a single-point tower measurement - Qi, Yongfeng; Shang, Xiaodong; Chen, Guiying; Gao, Zhiqiu; Bi, Xueyan; Yu, Linghui; Mao, Huabin (Frontiers in Earth Science, 2024)
Surface energy balance has always been a goal of those studying the Earth’s climate system. However, many studies have demonstrated that turbulent heat fluxes are usually underestimated by eddy covariance (EC) measurements, such that the energy balance is not closed. This study proposes a new perspective on calculating sensible heat flux based on the environmental temperature using EC. Using this approach, additional sensible heat fluxes were detected as outcomes of the vertical transportation of thermal structures in the atmospheric surface layer (ASL). For data obtained over a 40-day period over a grassland in Southern China, additional sensible heat flux observations exceeding 50 W m−2 were measured for 8 of the 40 days; smaller but still significant contributions were captured for another 11 days. In the proposed model, the difference between the mean and environmental temperature (∆T) and the local mean vertical velocity (w¯) serve as determinants for the additional flux, where the former can be deemed as the activity level of the thermal structures. A modeled underestimation of α[w¯] Ht of the total vertical sensible heat flux was revealed using our method, where α equals 3.55 for this study, Ht is the traditional EC results, and [w¯] is the non-dimensional w¯. Moreover, the additional flux usually showed large values in the daytime that were not detectable using the traditional EC method; this may help explain the energy imbalance problem in the ASL.